Development, Estimation And Validation Of Oseltamivir In Bulk And In Its Pharmaceutical Formulation By UV-VIS Spectroscopic Method - DUSMANT MEHER; Y.RAJESH; V.RAJA KUMAR; PROF. B.V.V.RAVI KUMAR; S.ARUN KUMAR (International Journal of Pharma and Bio Sciences, 2010)
The present study describes a simple, accurate, precise, specific and highly sensitive method for the determination of Oseltamivir present in pharmaceutical dosage forms. The method is validated for the determination of Oseltamivir in bulk and capsule dosage form. Oseltamivir is the newest addition to the group of H1N1 neuraminidase inhibitor and an Anti viral drug that slows the spread of influenza (flu) virus between cells in the body by stopping the new virus from chemically cutting ties with its host cell. The solvent used was 0.1N NaOH and the λmax or the absorption maxima of the drug was found to be 216nm. A linear response was observed in the range of 10100µg/ml with a regression coefficient of 0.999. The method was then validated for different parameters as per the ICH (International Conference for Harmonization) guidelines. This method can be used for the determination of Oseltamivir in quality control of formulation without interference of the excipients.